2016
DOI: 10.2147/copd.s102754
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of illness acceptance by patients with COPD and the prevalence of depression and anxiety in COPD

Abstract: BackgroundCOPD is a civilization disease. It affects up to 8%–10% of population >30 years of age. Coexistence of depression occurs in 20%–40% of patients with COPD. Depression and anxiety reduce compliance and worsen prognosis.ObjectiveThe aims of this study were to determine the degree of illness acceptance among patients with COPD, to examine the relation between disease acceptance and perceived anxiety and depression, and to verify which of the sociodemographic and clinical factors are associated with illne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 27 publications
(27 reference statements)
4
44
0
2
Order By: Relevance
“…Despite the well-known limits of adherence assessment by self-report tools, which may overestimate adherence,20 between one-third and one half of our patients report difficulties in adhering to behavioral prescriptions, thus stressing the necessity to intervene specifically on these aspects. Regarding disease perception, one-third of our patients struggle with DA and adaptation as shown in previous studies 33. On the other hand, most of them report that they live in a supportive environment in line with the WHO ICF model, which stresses the necessity to assess the environmental factors, both as barriers and as facilitators, when dealing with a chronic disease such as COPD 34…”
Section: Discussionsupporting
confidence: 57%
“…Despite the well-known limits of adherence assessment by self-report tools, which may overestimate adherence,20 between one-third and one half of our patients report difficulties in adhering to behavioral prescriptions, thus stressing the necessity to intervene specifically on these aspects. Regarding disease perception, one-third of our patients struggle with DA and adaptation as shown in previous studies 33. On the other hand, most of them report that they live in a supportive environment in line with the WHO ICF model, which stresses the necessity to assess the environmental factors, both as barriers and as facilitators, when dealing with a chronic disease such as COPD 34…”
Section: Discussionsupporting
confidence: 57%
“…Studies from the literature do not confirm any association between age and acceptance of illness;14,25 however, Uchmanowicz et al reported an insignificantly lower acceptance of illness in older patients who had additional burdens 13. The significant negative impact of age on illness acceptance shown by our study draws attention to the fact that elderly people are worse candidates for surgical treatment than younger ones, not only in terms of worse general health condition, longer convalescence, and longer wound healing process,29 but also in terms of metal attitude to such treatment as confirmed here by their lower level of acceptance of illness.…”
Section: Discussionmentioning
confidence: 96%
“…COPD, by profoundly impacting the patient’s quality of life, poses great socio-economic burden for individual patients, their families, and society 1,2. COPD primarily worsens quality of life by developing chronic, progressive dyspnea and consequent limitation of physical activity 3.…”
Section: Introductionmentioning
confidence: 99%